2022
DOI: 10.3389/fphar.2022.989139
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the potential active ingredients of Qi-Yu-San-Long decoction for anti-oxidation, inhibition of non-small cell lung cancer based on the spectrum-effect relationship combined with chemometric methods

Abstract: Qi-Yu-San-Long decoction (QYSLD), a traditional Chinese medicine (TCM) prescription, consisting of ten types of herbal medicine which has significant clinical efficacy in the treatment of non-small cell lung cancer (NSCLC). However, the bioactive ingredients of QYSLD remain unclear, due to their “multi-ingredients” and “multi-targets” features. This study aimed to construct a spectrum-effect correlation analysis model and screen the potential active components of QYSLD. A fingerprint method based on ultra-high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The variable importance in projection (VIP) indicates the degree of contribution. In general, a VIP value higher than 1 indicates a significant contribution to the PLSR model 29 . For the analysis of the activity results of the CR samples, the positive or negative regression coefficients indicated that the compounds were positively or negatively correlated with the antioxidant activity, and we found that peaks 1, 3, 4, 6, 7, 8, 9, and 10 were positively correlated with the antioxidant activity (Figure 7B).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The variable importance in projection (VIP) indicates the degree of contribution. In general, a VIP value higher than 1 indicates a significant contribution to the PLSR model 29 . For the analysis of the activity results of the CR samples, the positive or negative regression coefficients indicated that the compounds were positively or negatively correlated with the antioxidant activity, and we found that peaks 1, 3, 4, 6, 7, 8, 9, and 10 were positively correlated with the antioxidant activity (Figure 7B).…”
Section: Resultsmentioning
confidence: 78%
“…In general, a VIP value higher than 1 indicates a significant contribution to the PLSR model. 29 For the analysis of the activity results of the CR samples, the positive or negative regression coefficients indicated that the compounds were positively or negatively correlated with the antioxidant activity, and we found that peaks 1,…”
Section: Fingerprint-effect Correlation Analysismentioning
confidence: 72%
“…Indeed, as a TCM‐based therapeutic, T‐QY305, follows the same path, and each of its herbal components can be classified in a category, namely: “ Jun ”‐ Astragalus membranaceus , “ Chen ”‐ Lonicera japonica / Angelica sinensis , “ Zuo ”‐ Licorice , “ Shi ”‐ centipede . Precisely due to the “multi‐ingredients” and “multi‐targets” features of Chinese medicine formula, [ 24 ] the boiling process could generate self‐assembled nanomaterials, which did not require additional carrier and acted as a whole system, making up for the shortcomings of a single small molecule compound. [ 9a ] Hence, we suggested that T‐QY305's ability to suppress cutaneous adverse reaction and diarrhea originates from its subunit nanostructure N‐QY305, in which considered N‐QY305 as mediating the “ King ” (“ Jun ”) function in the treatment of adverse reactions, the decoction worked as “ Chen ”, the boiling process worked as “ Zuo ” and other components except for N‐QY305 worked as “ Shi ”.…”
Section: Resultsmentioning
confidence: 99%
“…It can use the chemical component signals in the existing fingerprints, extract complex information effectively through conversion and compression and establish the fuzzy mapping function relationship between these signals and the corresponding pharmacodynamic indexes. However, its principle is based on empirical risk minimization, which may lead to the risk of overfitting for small amounts of sample data [55].…”
Section: Association Based On Chemometric Methodsmentioning
confidence: 99%